AUTOMATED SYSTEM OF THE PROCESS OF ACCOUNTING AND CONTROL OF DIVICES OF THE RAILWAY AUTOMATION AND TELEMECHANICS - Astanaliev Elmurod; Baratov Dilshod (Scholar Express Journals, 2021)
Transport processes, especially from the point of view of the analysis of functioning of the automated technological complexes, including management and control of systems and devices of railway automation and telemechanics, are naturally formalized with application of schemes of mass service. the methodology of description of electronic document flow of technical documentation (EDMTD) in automation and telemechanics economy is based on allocation of the following components: control levels, technological chains according to the selected levels of hierarchy and algorithms of technological processes (TP) of the studied EDMTD. The formalized EDMTD scheme is synthesized on the basis of the generalized formalized scheme (GFS) of complex Queuing systems proposed by the authors in [4,5]. The content of the conceptual model (model description) is formed in accordance with the selected components based on the results of the survey of real processes of EDMTD. This allows us to move from a description model to a formalized scheme [6], which serves as the basis for the development of automated technology and simulation model (SM) of EDMTD, designed to assess the effectiveness of the system engineering decisions. A formal model is defined by a pair of disordered sets: a) a set of variables-parameters; b) a set of relations linking the values of these variables.
Keywords: Railway automation and telemechanics, electronic document management of technical documentation, graph theory, model of electronic document management, formal presentation of technical documentation